Memahami Proses Komunikasi Kelompok dalam Pengelolaan Konflik (Studi Etnografi pada Budaya Ma’ Kombongan dalam Upacara Rambu Solo’ Toraja) - Panggalo, Agimoto; Luqman, Yanuar (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This research was initiated by the change of motive in Rambu Solo’ Ceremony which would leads to conflict between family members involved in the ceremony. People of Toraja will have a family meeting called ma’ kombongan before they carry out rambu solo’ ceremony, this meeting will help settle the whole plan. Therefore this research wants to find an answer on how a family should manage conflict, since the goal of group communication is to solve problems. This research uses Functional Perspectif on Group Decision Making Theory, Coordinated Management of Meaning Theory and Thomas-Kilmann Conflict Mode Instrument Theory. Constructive paradigm is used in the research, with communication ethnographic approach. Data analysis on this research is separated into three steps; description, analysis and interpretation. Researcher gathers information from Paembongan Family whose sitting in Kampung Bua’ Burake, Makale, Tana Toraja, to observe how is the comunication process on every ma’ kombongan and how a family would manage conflicts. Using Thomas-Kilmann Conflict Mode Instrument Theory, shows that Paembongan family often relies on collaboration style in terms of rambu solo’ funding, dilema in mantunu tedong accommodation, and compromising between the inconsistency of aluk. The results from research’s site shows that every member of Paembongan Family has their own role in managing conflicts. There are some conflict triggers, including motive differences for conducting rambu solo’ ceremony and inconsistency of aluk. This research also found that Paembongan Family will improve their communication between members to reach effectiveness. Conflicts in Paembongan Family caused by a failure to interpret messages, also failure to understand communication context and situation. So, to overcome these conflict, requires all of family members’ participation to reach unison and conduct rambu solo’ ceremony.